Age-Related Changes in P-Glycoprotein Expression in Senescence- Accelerated Mouse - Wu, Bin; Ueno, Masaki; Onodera, Masayuki; Kusaka, Takashi; Huang, Cheng-long; Hosomi, Naohisa; Kanenishi, Kenji; Sakamoto, Haruhiko (Current Aging Science, 2009)
P-glycoprotein, the gene product of ATP-binding cassette, sub-family B (Abcb1), is a representative efflux transporter of cerebral vessels. It was recently reported that the expressions of P-glycoprotein and Abcb1 gene were increased in hippocampal vessels with blood-brain barrier (BBB) damage in stroke-prone hypertensive rats. SAMP8, senescence-accelerated mice with age-related deficits in memory and learning, are known to show age-related damage of BBB. Accordingly, in this study, we examined the P-glycoprotein expression and the gene expression (Abcb1a/b) by realtime quantitative reverse transcriptase-polymerase chain reaction (RT-PCR), Western blotting, and immunohistochemical techniques. SAMR1, which has a spontaneous retroviral insertional mutation in Abcb1a gene, was used to assess the effects of Abcb1a gene mutation. The brain samples of SAMR1 showed decreased expressions of P-glycoprotein and Abcb1a genes and increased expression of Abcb1b gene, compared with those of SAMP8 mice. The P-glycoprotein expression increased with aging in the brain samples of SAMP8, but not in those of SAMR1. The gene expressions of Abcb1a and Abcb1b increased with aging in the brain samples of SAMP8. Immunosignals of P-glycoprotein were seen in vessel walls, mainly in the cytoplasm of CD34-positive endothelial cells and partially in astrocytes, in all mice. These findings indicate that the expressions of Abcb1a and Abcb1b genes and their gene products, P-glycoprotein, were increased with aging in SAMP8, suggesting age-related response to prevent toxic substance from accumulating in the brains of SAMP8.
Keywords: mdr1